Management of radioactive waste gases from PET radiopharmaceutical synthesis using cost effective capture systems integrated with a cyclotron safety system. (7th July 2016) - Stimson, D H R; Pringle, A J; Maillet, D; King, A R; Nevin, S T; Venkatachalam, T K; Reutens, D C; Bhalla, R
Abstract: The emphasis on the reduction of gaseous radioactive effluent associated with PET radiochemistry laboratories has increased. Various radioactive gas capture strategies have been employed historically including expensive automated compression systems. We have implemented a new cost-effective strategy employing gas capture bags with electronic feedback that are integrated with the cyclotron safety system. Our strategy is suitable for multiple automated 18 F radiosynthesis modules and individual automated 11 C radiosynthesis modules. We describe novel gas capture systems that minimize the risk of human error and are routinely used in our facility.